Parafunctional oral habits and primary dentition characteristics in a group of preschool children from Tlaquepaque, Jalisco, Mexico. - José Francisco Murrieta-Pruneda; Yannette Concesa Velázquez-Jiménez; María Fernanda Yáñez-Acosta; María del Pilar Adriano Anaya; Tomás Caudillo Joya (Universidad de Concepción., 2019)
The aim of this study was to evaluate the relationship between some characteristics of primary dentition, and the frequency of parafunctional oral habits, with age and sex. Material and Methods: A cross-sectional study was carried out in a sample of 227 preschool children. Subjects' parents or guardians were asked to sign an informed consent form. The epidemiological survey consisted of an oral examination and the application of a questionnaire (Cronbach's alpha=0.881), after calibration of a dentist (Kappa=0.932). To measure the reliability of the questionnaire, Cronbach's alpha was calculated, and for the associations, Mantel and Haenszel Square Chi-square test and likelihood ratio for contingency tables greater than 2x2 values were calculated. Results: Type 2 arch (72.7%), mouth breathing (26.0%) and onychophagia (17.2%) were the risk factors observed more frequently in the group under study. The type of arch was the only variable that was associated with sex (X2MH=4.443, p=0.035). Conclusion: A significant proportion of the subjects had at least one risk factor that may alter the development of dental occlusion; consequently, the implementation of preventive actions in this population must be considered